Canaloplasty and trabeculotomy ab interno with the OMNI system combined with cataract surgery in open-angle glaucoma: 12-month outcomes from the ROMEO study. Issue 7 (July 2021) - Hirsch, Louis; Cotliar, Jeremy; Vold, Steven; Selvadurai, Deepan; Campbell, Anita; Ferreira, Gabriel; Aminlari, Ardalan; Cho, Andrew; Heersink, Sebastian; Hochman, Michael; Gallardo, Mark; Williamson, Blake; et al.
Abstract : Eighty-one patients were treated with OMNI system combined with cataract surgery by 12 surgeons at 11 centers. At 12 months, most (94%) had IOP of 18 mm Hg or less and significantly reduced medications. Abstract : Purpose: To provide safety and effectiveness outcomes 12 months postsurgically for sequential canaloplasty and trabeculotomy with the OMNI system combined with cataract surgery in mild-to-moderate open-angle glaucoma (OAG). Setting: Eleven ophthalmology practices and surgery centers located in 8 U.S. states. Design: Retrospective, multicenter, single arm. Methods: Twelve surgeons contributed 81 patients meeting eligibility criteria: OAG, 12-month follow-up, and medicated intraocular pressure (IOP) 36 mm Hg or less on 4 or less medications preoperatively. Analysis was stratified by baseline IOP: more than 18 mm Hg (Group 1) and 18 mm Hg (Group 2) or less. Success was defined as proportion with 20% reduction or greater in IOP or IOP between 6 and 18 mm Hg (inclusive) and on the same or fewer medications without secondary surgical intervention (SSI). Other endpoints included mean IOP and medications at 12 months. Safety included corrected distance visual acuity and adverse events (AEs). Results: Of the 81 patients included, primary success was met by 79% in Group 1 and 81% in Group 2. The mean IOP was reduced in Group 1 (21.9 to 15.1 mm Hg, P < .0001) and remained controlled in Group 2 (14.1 to 13.4 mm Hg, P = .3177). Medications went from 2.0 ± 1.3 to 1.1 ± 1.1 in Group 1 and from 1.6 ± 1.3 to 0.9 ± 1.2 in Group 2. AEs were typical for cataract or angle surgery: mild inflammation (11%), IOP spikes (5%), and hyphema (4%). Four patients (5%) required an SSI. Conclusions: The OMNI system provided effective IOP reduction, sustained IOP control, and meaningful medication reduction for up to 12 months postoperative.